2011
DOI: 10.1016/s2221-1691(11)60065-8
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic sensitivity pattern of bacterial pathogens in the intensive care unit of Fatmawati Hospital, Indonesia

Abstract: Most bacteria isolated from ICU of Fatmawati Hospital Jakarta Indonesia were resistant to the third generation of cephalosporins, and quinolone antibiotics. Regular surveillance of antibiotic susceptibility patterns is very important for setting orders to guide the clinician in choosing empirical or directed therapy of infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
79
3
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 26 publications
18
79
3
10
Order By: Relevance
“…In the past few decades, MRSA and MDR-P. aeruginosa become an increasingly important pathogen in both hospitals and community settings [4,19] , MRSA and MDR-P. aeruginosa play an important role in the colonization and infection of hospitalized patients. These bacteria are often implicated in a variety of nosocomial infections including bacteremia, urinary tract infections, and nosocomial pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few decades, MRSA and MDR-P. aeruginosa become an increasingly important pathogen in both hospitals and community settings [4,19] , MRSA and MDR-P. aeruginosa play an important role in the colonization and infection of hospitalized patients. These bacteria are often implicated in a variety of nosocomial infections including bacteremia, urinary tract infections, and nosocomial pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, the predominant multi-resistant bacteria that causes the infection such as P. aeruginosa, Klebsiella pneumoniae, Escherichia coli and methicillin resistant Staphylococcus aureus (S. aureus) (MRSA) have been found in several hospitals in Indonesia [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Resistant S. aureus is more frequently associated with nosocomial infections in hospitals, and even in intensive care units (ICU) in many of the developing countries [35] . In antibiogram study for S. aureus isolates from meat origin, Heo et al reported 92.9% and 50% resistance of tetracycline and ampicillin respectively [15] .…”
Section: Discussionmentioning
confidence: 99%
“…High rate of resistance to cephalexin and also levofloxacin was detected among S. epidermidis isolates (18).…”
Section: Discussionmentioning
confidence: 96%